2007
DOI: 10.1007/s10562-007-9014-z
|View full text |Cite
|
Sign up to set email alerts
|

C2H2-SCR of NO over HZSM-5 affected by intracrystalline diffusion of NO x

Abstract: The influence of particle size of HZSM-5 zeolite on selective catalytic reduction of NO by acetylene (C 2 H 2 -SCR) was investigated. The zeolite with nano-particle behaved considerable higher activity than the micro-particle one for the reaction. It was revealed that the large difference in the activity for the C 2 H 2 -SCR of NO arising from the particle size of zeolite was not caused by limited intracrystalline diffusion of the reductant, but that of NO 2 , which was strongly supported by the adsorption res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…10(a)-(c)) beyond 0 9p/p o corresponds to larger inter-aggregated pores between the secondary particles. 46 The pore size distribution curves distributions. The smaller mesopores in the membrane represent the pores within the TiO 2 shell and the larger ones are from the formation of pores by the doping and calcination induced inter-aggregated pores.…”
Section: Nitrogen Adsorption-desorption Studiesmentioning
confidence: 99%
“…10(a)-(c)) beyond 0 9p/p o corresponds to larger inter-aggregated pores between the secondary particles. 46 The pore size distribution curves distributions. The smaller mesopores in the membrane represent the pores within the TiO 2 shell and the larger ones are from the formation of pores by the doping and calcination induced inter-aggregated pores.…”
Section: Nitrogen Adsorption-desorption Studiesmentioning
confidence: 99%
“…It has been demonstrated that numerous catalysts such as zeolitic oxide, base metal/oxides, and noble metal catalysts are effective for NOx removal by HC-SCR in the presence of excess oxygen [2][3][4][5][6]. Among them, alumina-supported silver (Ag/Al2O3) is a particularly promising catalyst for practical application [1,[7][8][9].…”
Section: Introductionmentioning
confidence: 99%